Analisis Penguasaan Kosa Kata Bahasa Arab Siswa Kelas VII B Akhwat MTS Jabal An-Nur Al-Islami - Sely Agustianingsih; Kasmudi; M Zaky Sya’bani (Program Studi Pendidikan Bahasa Arab, 2023)
This research is based on the mastery of Arabic vocabulary owned by the seventh grade students of MTs Jabal An Nur Al-Islami Bandar Lampung. (mufradat) Arabic for the seventh grade students of MTs Jabal An-Nur Al-Islami? - Islamic? While the purpose of this study is to describe the mastery of vocabulary (mufradat) class VII B Akhwat MTs Jabal An Nur Al-Islami and to find out the factors that support and hinder the mastery of Arabic vocabulary (mufradat) of class VII B students of Akhwat MTs Jabal An-Nur Al-Islami. The type of research that the researcher uses is descriptive qualitative research. The subject of this research is class VII B Akhwat MTs Jabal An-Nur Al-Islami with a total of 30 students. After conducting research, analyzing, the conclusions received, the level of mastery of Arabic vocabulary for class VIIB students of MTs Jabal An-Nur Al-Islami is good, with a percentage of 61.75% of students who memorize fluently and have mastered memorized vocabulary. Some of the supporting and inhibiting factors for mastering Arabic vocabulary for students of class VII B akhwat MITS Jabal An-Nur Al-Islami Bandar Lampung include supporting factors: student interest and motivation, students' habits of learning Arabic, students studying the material first, learning In the first hour of Arabic, the teacher arranges learning and an environment that requires communicating in Arabic. The inhibiting factor: students are less confident in speaking Arabic. lack of concentration, lack of use of learning media. Buru's indiscipline with time.